2014
DOI: 10.1007/s00259-014-2904-6
|View full text |Cite
|
Sign up to set email alerts
|

The value of 18F-fluoride PET/CT in the assessment of screw loosening in patients after intervertebral fusion stabilization

Abstract: (18)F-Fluoride PET/CT imaging is useful for the diagnosis of screw loosening in patients with persistent symptoms after intervertebral fusion stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…An increased uptake has also been registered in other studies of cases with screw-loosening with a specificity of 97.4% in patient-based analysis [ 40 ]. A relationship with painful pseudarthrosis was suggested by Peters et al in a retrospective series of 36 patients, because after surgery 18F-NaF activity was reported to be significantly higher in patients with worse functional scores [ 41 ]. Abnormal foci of uptake appear to be related to the patient’s source of pain and could be located at various sites involved in arthrodesis (cages, screws, rods, or bone grafts) helping surgeons to choose the best management and strategy if a surgical revision is considered mandatory [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased uptake has also been registered in other studies of cases with screw-loosening with a specificity of 97.4% in patient-based analysis [ 40 ]. A relationship with painful pseudarthrosis was suggested by Peters et al in a retrospective series of 36 patients, because after surgery 18F-NaF activity was reported to be significantly higher in patients with worse functional scores [ 41 ]. Abnormal foci of uptake appear to be related to the patient’s source of pain and could be located at various sites involved in arthrodesis (cages, screws, rods, or bone grafts) helping surgeons to choose the best management and strategy if a surgical revision is considered mandatory [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this series, implant stability and fusion were finally confirmed by radiological exams (X-rays of CT), helping us to adequately validate our results. As described by previous studies, the presence of pseudarthrosis, subsidence, or implants loosening could result in abnormal uptake, increasing over time and helping to discriminate between asymptomatic and symptomatic cases requiring revision [ 41 , 42 , 43 ]. According with our preliminary results [ 36 ], the use of custom-made TTCs is confirmed to represent a promising approach in order to achieve good stability promoting active osteo-integration and fusion, while minimizing subsidence rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, CT scan is still the only accepted method in literature to evaluate osseous progression after spinal fusion surgery, to determine screw positions, to confirm the integrity of instrumentation elements, to detect suspicious complications, to investigate new disease and / or disease progression (5,8,13,14). It is believed that the screw loosening aetiology is multifactorial and may depend on the patient characteristics (such as age, gender, weight bearing), strength type of screws, operation technique, and the length of the spinal segments to be fused (5,8,15). Indeed, On the other hand, screw loosening is thought to occur most frequently in patients with thoracolumbar posterior instrumentation (4,18,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…121 Spinal orthopedics is another area that may benefit from NaF-PET, which may have a role in predicting healing and identifying complications such as nonunion, pseudarthrosis, infection, and hardware loosening. [126][127][128][129][130][131] In pediatrics, Grant 27 reported utility in determining the cause of pain in children who underwent spinal fusion surgery for scoliosis. Fischer and colleagues 132 studied 20 patients who underwent cervical or lumbar intercorporal fusion and found that increased NaF activity could be visualized in cervical cages for up to 8 years after intervention and up to 10 years in lumbar cages (Fig.…”
Section: Orthopedic Complicationsmentioning
confidence: 99%